2021
DOI: 10.12968/bjmh.2020.0014
|View full text |Cite
|
Sign up to set email alerts
|

Bitesized Teaching: educational futures for mental health training

Abstract: Background/Aims Bitesized Teaching is an initiative that has worked successfully in Yorkshire and Derbyshire Mental Health Services for the last 5 years. It traditionally involves the delivery of high-impact, 10-minute tutorials on physical health topics, which take place once a week in the ward lunchtime handover period. This study evaluates an extension to the Bitesized Teaching scheme that incorporates delivering mental health-focused teaching topics to clinical staff on medical wards. Methods Bitesized Tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Dunleavy et al pointed out that physical health instruction can promote students' motivation and initiative towards physical health [ 2 ]. Thompson et al, who conducted a study in collaboration with experts in psychological aspects, stated that physical health instruction can not only reduce students' chances of sports injuries but also enhance students' mental health [ 3 ]. Chun and Yin found that students' physical health is poor, and physical health education is important for improving students' physical fitness [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dunleavy et al pointed out that physical health instruction can promote students' motivation and initiative towards physical health [ 2 ]. Thompson et al, who conducted a study in collaboration with experts in psychological aspects, stated that physical health instruction can not only reduce students' chances of sports injuries but also enhance students' mental health [ 3 ]. Chun and Yin found that students' physical health is poor, and physical health education is important for improving students' physical fitness [ 4 ].…”
Section: Introductionmentioning
confidence: 99%